2019
DOI: 10.1111/phn.12656
|View full text |Cite
|
Sign up to set email alerts
|

Using a quality improvement model to enhance community/public health nursing education

Abstract: Background Population‐focused practice is an essential component of baccalaureate nursing education. The specialty of community/public health nursing (C/PHN) emphasizes prevention and focuses on the multiple determinants of health to improve population health outcomes. This project addressed two problems. How to: (a) Standardize C/PHN education by utilizing a set of competencies, and (b) Evaluate learning outcomes after using the competencies. Method As collaborative team applied community/public health compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Research articles classified under the “others” category had the following six new subtypes: “use the OS data for assessment for those other than clients,” 15 “use the OS data as structured data,” 16 “encode by the OS code,” 17–28 “adopt the OS framework,” 29–37 “clinical information system,” 38–43 and “review article.” 9,44,45 …”
Section: Resultsmentioning
confidence: 99%
“…Research articles classified under the “others” category had the following six new subtypes: “use the OS data for assessment for those other than clients,” 15 “use the OS data as structured data,” 16 “encode by the OS code,” 17–28 “adopt the OS framework,” 29–37 “clinical information system,” 38–43 and “review article.” 9,44,45 …”
Section: Resultsmentioning
confidence: 99%
“…Nursing is a highly relevant subject, and the education and training of community nursing, especially nursing related to the aged, is taken seriously in foreign countries. Nursing students’ skills and professional values are improved by participating in various community nursing practices, enhancing their competence, and developing a professional identity [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Joyce et al (33) identified an improvement in the process of teaching in nursing using continuous assessment. In terms of the few studies of this matter carried out in our own area, our results confirm those of Fernández Ponce et al, (34) in that continuous assessment encourages the involvement of students and increases their satisfaction.…”
Section: Discussionmentioning
confidence: 99%